Diazotrophic Bacteria Is an Alternative Strategy for Increasing Grain Biofortification, Yield and Zinc Use Efficiency of Maize - Jalal, Arshad [UNESP]; Oliveira, Carlos Eduardo da Silva [UNESP]; Fernandes, Henrique Benetasse [UNESP]; Galindo, Fernando Shintate; Silva, Edson Cabral da; Fernandes, Guilherme Carlos [UNESP]; Nogueira, Thiago Assis Rodrigues [UNESP]; Carvalho, Pedro Henrique Gomes de [UNESP]; Balbino, Vinícius Rodrigues [UNESP]; Lima, Bruno Horschut de [UNESP]; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP] (MDPI, 2022)
Biofortification of cereal crops with zinc and diazotrophic bacteria is a sustainable solution to nutrient deficiency and hidden hunger. The inoculation of staple grain crops such as maize is increased with reducing productivity losses while improving nutrition and use efficiency under climatic extremes and weathered soils of tropical savannah. Therefore, objectives of our study were to evaluate the influence of seed inoculation with diazotrophic bacteria (No inoculation–Control, Azospirillum brasilense, Bacillus subtilis, and Pseudomonas fluorescens) together with residual effect of soil Zn (absence and presence) on growth, yield, Zn nutrition, Zn use efficiencies, and intake of maize in 2019 and 2020 cropping seasons. The inoculation of B. subtilis increased hundred grain mass and yield (14.5 and 17%), while P. fluorescens under residual Zn fertilization has improved shoot and grain Zn concentration in shoot (29.5 and 30.5%). and grain (25.5 and 26.2%), while improving Zn accumulation in shoot (33.8 and 35%) and grain (37.2 and 42%) of maize. The estimated Zn intake in maize was also increased with A. brasilense inoculation and residual Zn application. The Zn use efficiencies including Zn use efficiency, agro-physiological, and utilization efficiency was increased with B. subtilis, while applied Zn recovery was increased with A. brasilense inoculations under residual Zn fertilization. Zinc use efficiency was increased by 93.3 and 397% with inoculation of B. subtilis regardless of Zn application. Therefore, inoculation with B. subtilis and P. fluorescens along residual Zn fertilization is considered the most effective and sustainable strategy for agronomic biofortification of maize under harsh tropical conditions of Brazil.
Keywords: agronomic biofortification; inoculation; productivity; Zea mays L; zinc efficiencies; zinc nutrition; zinc uptake